Peningkatan Kompetensi Guru Desa Tirak melalui Pelatihan AI (ChatGPT dan Gamma.app) untuk Penyusunan Perangkat Ajar Digital - Riyanto, Slamet; Nur Luthfi Azis, Muh; Ilham Abimanyu, Muhammad (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the competence of educators in the development of digital teaching tools through the integration of artificial intelligence (AI). The target of the activity is teachers in Tirak Village, Kwadungan District, Ngawi Regency, East Java Province, which will be held on November 29-30, 2025. The implementation method includes interactive lectures, demonstrations, project-based practices, and intensive assistance in the use of the ChatGPT application for the preparation of teaching tool components (learning objectives, summary materials, activities, LKPD, assessments, and rubrics) as well as Gamma.app for making presentations/visual materials. Evaluation is carried out using pre-test and post-test, accompanied by the assessment of digital teaching tool products through weighted rubrics. The results of the activity showed an increase in participants' understanding of the responsible use of AI, marked by an increase in post-test scores compared to pre-tests, as well as the ability of participants to produce at least one digital teaching tool package that is more structured and attractive. The activity showed that AI integration training using ChatGPT and Gamma.app effectively improve teachers' skills in compiling digital teaching tools that are ready to be applied in the classroom, with follow-up recommendations in the form of periodic assistance to strengthen the quality of assessment and final editing of teaching tools.